Boosting Work Performance in The Digital Era: The Crucial Role of Job Satisfaction at PT Brantas Abipraya - Muhamad Ulul Azmi; Rufika Trianto; Suseno; Prasetya, Agustian Budi (Universitas Negeri Semarang, 2024)
This study aims to analyze the impact of work engagement and job satisfaction on the work performance of employees at PT Brantas Abipraya. Utilizing a quantitative-explanatory method, data were collected from 316 respondents who are permanent employees of the company. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that work engagement has a positive and significant effect on work performance. Conversely, smartphone use at night has a significantly negative impact on both job satisfaction and work performance. Additionally, emotional exhaustion was found to negatively affect both work performance and job satisfaction. However, job satisfaction can mediate the relationship between smartphone use and emotional exhaustion on work performance. These findings provide practical implications for companies to regulate smartphone use outside of working hours and to offer adequate emotional support to employees to enhance their performance and well-being.